2020
DOI: 10.13189/ujer.2020.080322
|View full text |Cite
|
Sign up to set email alerts
|

Teacher Competencies for Dyslexia Students

Abstract: This study aims to identify the competencies that teachers have in dealing with dyslexic students. Method: The type of research used is quantitative which uses a research design survey that is strengthened by the results of interviews to support the results of quantitative data. Where the total number of samples from this study were 91 teachers taken based on the total sampling technique. Data were then analyzed with the help of the SPSS 21 application to look for descriptive statistics in the form of mean, me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 20 publications
0
1
0
Order By: Relevance
“…En una investigación realizada por Muin et al (2020) se muestra que los docentes tienen la capacidad de identificar y trabajar con un estudiante con dislexia, con una categoría de 64,8 % (59 de 91). La educación inclusiva ha mejorado en los últimos años gracias a los programas del gobierno que han capacitado a los maestros para atender las necesidades de los estudiantes con discapacidad.…”
Section: Discussionunclassified
“…En una investigación realizada por Muin et al (2020) se muestra que los docentes tienen la capacidad de identificar y trabajar con un estudiante con dislexia, con una categoría de 64,8 % (59 de 91). La educación inclusiva ha mejorado en los últimos años gracias a los programas del gobierno que han capacitado a los maestros para atender las necesidades de los estudiantes con discapacidad.…”
Section: Discussionunclassified
“…Teacher performance is an aspect that figuring capability in preparing learning plans, carrying out the learning process and implementing learning assessments in accordance with the objectives to be achieved (Bakar, 2018;Muin, Riyanto, & Wibowo, 2020;Rinantanti, Bin-Tahir, & Aminah, 2019). Departing from this, the teacher performance appraisal (PKG) of each rubric/activity item is divided into the first three indicators compiling learning plans (RPP Identity, Components, Indicators, Objectives, Learning Materials, Learning Methods, Learning Resources, Preliminary Activities, Activities core, Closing Activity, Assessment).…”
Section: Discussionmentioning
confidence: 99%
“…In principle, a competent teacher is a teacher who can provide great benefits to his or her students (Sulaiman & Ismail, 2020) and this statement is following the results of a study of 91 teachers, which found that teachers who have excellent competence can handle students who have problems in learning and reading (dyslexia) with the ability category, namely the good category, which is 64.8% (Muin et al, 2020). Teacher competence has a broad scope which consists of pedagogic competence, personal competence, and social and professional competence (Zulfah & Sholeh, 2021).…”
Section: Description Of Teachers' Digital Literacy Competencymentioning
confidence: 98%